Early to mid-term outcome of Oxinium on Verilast highly cross-linked polyethylene bearing surface in uncemented total hip arthroplasty. Issue 6 (November 2019) - Sobti, Anshul S; Busch, Constant A; Afolayan, John O; Michael, Dean; Chana, Rishi
Introduction: We report 5- to 10-year clinical and radiological outcomes of a series of uncemented Oxinium on Verilast (highly cross-linked polyethylene liners) total hip replacements (THAs) using the Anthology stem and R3/Reflection cup system. Methods: 116 THAs were performed by 2 senior authors in 104 patients from 2005 to 2009. The mean age at time of operation was 63.8 (45–80) years. The average length of follow-up was 8.8 years. At final data collection 12 patients had died (13 THAs) and 3 patients (3 THAs) were lost to follow-up. Results: In the remaining 100 THAs, the preoperative Harris Hip Score of 39 improved to 91 and Oxford Hip Score improved from 16 to 44 (mean at 5 to 10 years). 100 THAs were available for radiographic analysis: all had stable bony ingrowth of both the stem and cup. Dorr's methods for wear in the 100 THAs showed an average wear <0.01 mm/year and no osteolysis; only 1 case showed 0.22 mm/year with some proximal femoral osteolysis but no cup lesions. There were no dislocations or revisions, survivorship in this series for both components for any cause as an endpoint was 100%. 1 intraoperative calcar fracture was sustained and treated with a cerclage wires, 2 peri-prosthetic fractures occurred and were treated with open reduction and fixation, both healed well with excellent outcomes. Discussion: The study has shown good clinical and radiological outcomes at 5–10 years and supports existing data on the potential benefits of this bearing performance in literature.